Does Mandating Nondiscrimination in Hiring Practices Influence Women's Employment? Evidence Using Firm-level Data - Amin, Mohammad (Taylor and Francis, 2015)
This study explores the relationship between mandating a nondiscrimination clause in hiring practices along gender lines and the employment of women versus men in fifty-eight developing countries. Using data from the World Bank's Enterprise Surveys (2006–10), the study finds a strong positive relationship between the nondiscrimination clause and women's relative to men's employment. The relationship is robust to a large number of controls at the firm and country level. Results also show sharp heterogeneity in the relationship between the nondiscrimination clause and women's versus men's employment, with the relationship being much bigger in richer countries and in countries with more women in the population as well as among relatively smaller firms.